2017
DOI: 10.1111/jop.12570
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of oral submucous fibrosis in Taiwan: A nationwide population‐based retrospective cohort study

Abstract: Oral submucous fibrosis patients exhibited a significantly higher risk of malignant transformation than those without OSF. OL could enhance malignant transformation in patients with OSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 15 publications
1
60
1
Order By: Relevance
“…Oral leukoplakia, oral erythroplakia, and oral lichen planus are usually associated with OSF and increase the risks of oral malignancy. According to a recent study among 778 cases of OSF in Taiwan, the incidence of malignant transformation was 9.13%, with an average duration of 13 years (Yang et al., ). Meanwhile, the transformation rate was 7.6% after 17 years of follow‐up in an Indian study (Murti et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Oral leukoplakia, oral erythroplakia, and oral lichen planus are usually associated with OSF and increase the risks of oral malignancy. According to a recent study among 778 cases of OSF in Taiwan, the incidence of malignant transformation was 9.13%, with an average duration of 13 years (Yang et al., ). Meanwhile, the transformation rate was 7.6% after 17 years of follow‐up in an Indian study (Murti et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…12,32 A study using the Taiwan National Health Insurance database indicated that the malignant development rate of OSF accompanied by leukoplakia (15.7%) was higher than that of OSF alone (7.0%). 33 Of the 27 OSF cases with accompanying leukoplakia in this study, 48% underwent surgery. As a result, the carcinoma development rate in OSF cases with accompanying leukoplakia was 18.5%, which was significantly higher than the 4.6% found in patients with OSF alone.…”
Section: Discussionmentioning
confidence: 77%
“…Oral submucous fibrosis (OSF) is one of the oral precancerous lesions with high incidence of malignant transformation and rising global prevalence . The malignant transformation rate of OSF has been reported to be around 9%~26% . Therefore, to explore the molecular mechanisms of this disease may help us identify new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…2 The malignant transformation rate of OSF has been reported to be around 9% 26%. 3,4 Therefore, to explore the molecular mechanisms of this disease may help us identify new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%